Meeting the needs of agribusiness students in an ESP-reading context - Dyah Aju Hermawati (Journal of Research on English and Language Learning (J-REaLL), 2022)
This study explored the needs for English for Specific Purposes (ESP) among the Agribusiness students in Jember State Polytechnic. It investigated the students' attitudes towards English for Specific Purposes (ESP) and their readiness for it. The study focuses on the issue of designing a suitable core course of English for Specific Purposes that introduces ESP through academic reading. The study is based on the investigation of the learners' needs. The aim of the study is to propose a suitable course in which ESP can be integrated or injected within the regular English for General Purpose classrooms in order to facilitate the students' academic progress within agribusiness's current issues.